Evaluation Of Fiber Reinforced Asphalt Mixtures And Sensitivity Analysis For Airport Pavement Maintenance And Rehabilitation Practices - Tan, Jeff Fei (Universiti Sains Malaysia, 2022)
In Malaysia, use of the fiber as a modifier in asphalt mixtures is one of the options to prolong pavement life. Application of the fiber such as Super Fiber Mix (SFM) has covered more than 3.3 million square areas for road construction. However, the applications of the SFM in runway construction are still limited. For that reason, there are limited reports that discussed the effects of the SFM on the PLUS asphalt concrete wearing course (ACWC 20) and Malaysian Public Work Department’s asphalt concrete binder course (ACBC 28) gradations. These gradations provide good pavement structural support to cater to aircraft loads. In this research, the conventional asphalt mixture and modified asphalt mixture were prepared. Conventional asphalt mixture 60/70 penetration grade is used throughout the study. Marshall mix design was carried out to determine the Optimum Binder Content (OBC) for both ACWC20 and ACBC28. The OBCs for the ACWC20 and ACBC28 is 5.1% and 4.6% respectively. At the same OBCs, the SFM was added to reinforced asphalt mixture. Modified asphalt mixture is modified with SFM which consists of polyolefin and aramid fibers which contribute less than 0.1% of the total weight of the mixture. Several tests are carried out to evaluate the performance of SFM additives to the asphalt mixture. The tests are Marshall Stability and Flow test, Indirect Tensile Strength Test, Resilient Modulus Test, and Hamburg Wheel Tracking Test. All laboratory tests have proved the additive of SFM in asphalt mixture has improved the mixture performance. The Marshall Stability of modified asphalt, MA is 20% and 35% higher than conventional asphalt CA for ACWC20 and ACBC28 respectively. The flow value of modified asphalt is lower than conventional asphalt as the addition of SFM has increased the deformation resistance of the asphalt mixture. The ITS value for MA increased by 39% and 30% for ACWC20 and ACBC28 respectively.The SFM has improved the asphalt resistance to cracking. In resilient modulus test, the resilient modulus of modified of modified asphalt is 30% and 31% better than conventional asphalt for ACWC20 and ACBC28 respectively. Furthermore, the rut depth of MA and CA are 4.72mm and 6.60mm respectively which indicates MA has better rutting resistance than CA. Additionally, Sensitivity analysis of the FAARFIELD was carried out to determine the effect of pavement layer thicknesses and modulus values on the pavement life (year). The result of the analysis software shows that the thickness of pavement has a significant impact on pavement life. The thicker the pavement thickness, the higher the pavement life. Increasing the thickness of wearing course by 0.6 inches can extend the pavement life by more than 10 years from the thickness analysis of FAARFIELD. On the other hand, the pavement life increased as the resilient modulus of pavement increased. In the resilient modulus analysis, 33.5% higher modulus value of wearing course resulted in 7.3 years higher pavement life. The data reveals that the addition of SFM which improved the resilient modulus has increased the pavement life. In short, the higher the resilient modulus of pavement, the longer the pavement life.